Understanding the properties, wave drivers, and impacts of electron microburst precipitation: Current understanding and critical knowledge gaps - Elliott, Sadie S.; Breneman, Aaron; Colpitts, Christopher; Bortnik, Jacob; Jaynes, Allison; Halford, Alexa; Shumko, Mykhaylo; Blum, Lauren; Chen, Lunjin; Greeley, Ashley; Turner, Drew (Frontiers in Astronomy and Space Sciences, 2022)
Microbursts are impulsive (<1s) injections of very energetic to relativistic electrons (energies from a few keV to MeV) into Earth’s atmosphere. They are important because they may represent a major loss process for the outer radiation belt (Ripoll et al., 2020). Understanding and quantifying the underlying causes and consequences plus relative importance of microburst precipitation represent outstanding questions in radiation belt physics and may have significant implications ranging from space weather to atmospheric chemistry. Chorus waves are the likely dominant cause of microburst precipitation, but important questions remain regarding the exact nature of the resonance generating the microbursts and the overall importance of the precipitation. These important questions are limited by lack of systematic coordination of simultaneous observations of causative waves in the magnetosphere and resulting precipitating particles at low altitudes. Multi-spacecraft missions dedicated to answering these questions, themselves required to make progress in radiation belt physics, are critical.